Influence of early childhood parental hostility and socioeconomic stress on children’s internalizing symptom trajectories from childhood to adolescence - Williams, Lue; Oro, Veronica; Blackwell, Courtney K.; Liu, Chang; Miller, Elizabeth B.; Ganiban, Jody; Neiderhiser, Jenae M.; DeGarmo, David S.; Shaw, Daniel S.; Chen, Tong; Natsuaki, Misaki N.; Leve, Leslie D. (Frontiers in Psychiatry, 2024)
Introduction Children and adolescents with elevated internalizing symptoms are at increased risk for depression, anxiety, and other psychopathology later in life. The present study examined the predictive links between two bioecological factors in early childhood—parental hostility and socioeconomic stress—and children’s internalizing symptom class outcomes, while considering the effects of child sex assigned at birth on internalizing symptom development from childhood to adolescence. Materials and Methods The study used a sample of 1,534 children to test the predictive effects of socioeconomic stress at ages 18 and 27 months; hostile parenting measured at child ages 4–5; and sex assigned at birth on children’s internalizing symptom latent class outcomes at child ages 7–9, 10–12, 13–15, and 16–19. Analyses also tested the mediating effect of parenting on the relationship between socioeconomic stress and children’s symptom classes. Other covariates included parent depressive symptoms at child ages 4–5 and child race and ethnicity. Results Analyses identified three distinct heterogenous internalizing symptom classes characterized by relative symptom levels and progression: low (35%); moderate and increasing (41%); and higher and increasing (24%). As anticipated, higher levels of parental hostility in early childhood predicted membership in the higher and increasing symptom class, compared with the low symptom class (odds ratio (OR) = .61, 95% confidence interval (CI) [.48,.77]). Higher levels of early childhood socioeconomic stress were also associated with the likelihood of belonging to the higher-increasing symptom class compared to the low and moderate-increasing classes (OR = .46, 95% CI [.35,.60] and OR = .56, 95% CI [.44,.72], respectively). The total (c = .61) and direct (c’ = .57) effects of socioeconomic stress on children’s symptom class membership in the mediation analysis were significant (p <.001). Discussion Study findings suggest that intervening on modifiable bioecological stressors—including parenting behaviors and socioeconomic stressors—may provide important protective influences on children’s internalizing symptom trajectories.